Strategi Operasional dalam Persfektif Koperasi Desa Merah Putih - Ngakan Made Karya Mardika; Nia Puspita Hapsari; Daman Sudarman; Novita Kurniawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to examine, and design an efficient operational strategy at the Merah Putih Village Cooperative through a collaboration of the Just-In-Time (JIT), and Total Quality Management (TQM) approaches. The background of this study is based on the problem of low operational efficiency of cooperatives which has an impact on the mismatch between member demand and cooperative service capacity. The main objective of the study is to formulate a collaborative model of JIT and TQM that can increase productivity, reduce waste, and ensure the quality of cooperative services and products. The methodology used is a qualitative approach with a case study, involving field observations, in depth interviews with cooperative administrators and members, and internal documentation analysis. Data analysis techniques are carried out through a thematic approach and triangulation to obtain the validity of the results. The results of the study indicate that the application of the JIT principle can minimize unproductive inventory, while the application of TQM encourages a work culture that is oriented towards continuous improvement and member satisfaction. The collaboration of these two strategies has been proven to be able to increase the operational efficiency of cooperartive by up to 35%, accelerate the service cycle, and significantly reduce the level of member complains. The implications of these findings indicate that village cooperatives can apply a modern management approach by adjusting it to the local context, as well as the importance of continuous training for cooperative human resources. The proposed JIT - TQM corroborative model can be used as a reference for the cooperative in increasing competitiveness and operational efficiency in the people’s economic sector.